2017
DOI: 10.1001/jamapediatrics.2016.4798
|View full text |Cite
|
Sign up to set email alerts
|

Using Patient-Centered Care After a Prenatal Diagnosis of Trisomy 18 or Trisomy 13

Abstract: atient satisfaction with health care is an increasingly significant concern. In 2001, the Institute of Medicine introduced a comprehensive strategy to improve health care in the United States. A key aim of this proposal is patient-centered care (PCC), defined as "providing care that is respectful of and responsive to individual patient preferences, needs, and values and ensuring that patient values guide all clinical decisions." 1(p6) Based on a comprehensive analysis of patient focus group data, 4 core conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…On many occasions, therefore, the problem is approached from a biologicist standpoint, focusing exclusively on the chromosomopathy, without contemplating having a child with disability or evaluating the option of adoption (Vargas Aldecoa, Martin Conty, Conty Serrano, & Fernandez Perez, ). To achieve satisfactory communication, there must be a patient‐centred approach, with a biopsychosocial understanding that recognises the need to consider not only the disease but also the personal experience (Haug, Goldstein, Cummins, Fayard, & Merritt, ). The main aim of the present study was to analyse the experience, described in their own words, of pregnant women given a diagnosis of chromosomopathy and/or foetal malformation, and who then legally terminated their pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…On many occasions, therefore, the problem is approached from a biologicist standpoint, focusing exclusively on the chromosomopathy, without contemplating having a child with disability or evaluating the option of adoption (Vargas Aldecoa, Martin Conty, Conty Serrano, & Fernandez Perez, ). To achieve satisfactory communication, there must be a patient‐centred approach, with a biopsychosocial understanding that recognises the need to consider not only the disease but also the personal experience (Haug, Goldstein, Cummins, Fayard, & Merritt, ). The main aim of the present study was to analyse the experience, described in their own words, of pregnant women given a diagnosis of chromosomopathy and/or foetal malformation, and who then legally terminated their pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences, familial, and religious beliefs are reported to be the main factors affecting attitudes toward invasive prenatal testing and pregnancy termination in fetal abnormalities. 13,14 In keeping with this consideration, we found that in 18.5% (10/54), karyotype analysis was not performed, even if there were multiple anomalies. All parents who accepted invasive testing opted for ToP after a positive karyotype result, except one with mosaic trisomy 13 and one with full trisomy 18, which ended in fetal demise.…”
Section: Discussionmentioning
confidence: 57%
“…Cardiac surgical offerings may be considered in the context of an interdisciplinary care team's shared exploration of the child's comorbidities and the family's understanding of overall prognosis, values, and decisional context. 37 Mixed methods research is recognised as transformative in capturing differing value commitments which can lead to dialogue across professional, personal, and ideological perspectives. This study adds to the recent dialogue by describing parental hopes and goals in pursuing cardiac surgical interventions.…”
Section: Resultsmentioning
confidence: 99%